Open-lung strategies and mechanical power during protective ventilation for laparoscopic anterior resection: a randomised controlled trial - Jing Guo; Chu-Ling Liu; Li-Zhen Zhang; Jing Li; Xiao-Ke Gu; Tian-Shuo Wang; Nan-Rong Zhang; Hong Li (Scientific Reports)
Abstract Higher intraoperative mechanical power (MP) is associated with increased postoperative pulmonary complications (PPCs). We hypothesised that periodic alveolar recruitment manoeuvres (PARM) alone, as an open-lung strategy for intraoperative protective ventilation, would reduce MP, thereby potentially mitigating PPCs. Seventy-five non-obese participants were equally allocated to either alveolar recruitment manoeuvres every 30 min alone (PARM group), or medium positive end-expiratory pressure (PEEP) of 6–8 cmH2O alone (PEEP group), or a combination of medium PEEP and PARM (combination group). As a result, the median (interquartile range, IQR) MP in the PARM group was lower than in the other groups (PARM, 4.34 [3.58–5.27]; PEEP, 6.47 [5.83–7.74]; combination, 6.32 [5.16–7.36] J min−1; P < 0.001). The median difference (95% confidence interval, 95% CI) of MP between the PARM and control group (combined PEEP and combination) was 2.05 (1.34–2.74) J min−1, with a significant reduction (32.2%, P < 0.001) in the PARM group. However, no clinical benefit (such as PPCs) was observed despite these physiological improvements. In conclusion, PARM alone as an open-lung strategy for protective ventilation leads to a 32.2% reduction in MP, compared with medium PEEP alone or a combination of PARM and medium PEEP. The association between PARM and PPCs warrant further investigations.